Settlement of Ulva zoospores on patterned fluorinated and PEGylated monolayer surfaces - Finlay, John A (Langmuir : the ACS journal of surfaces and colloids, 2008)
Various designs for coatings that resist the attachment of marine organisms are based on the concept of "ambiguous" surfaces that present both hydrophobic and hydrophilic functionalities as surface domains. In order to facilitate the optimal design of such surfaces, information is needed on the scale of the domains that the settling stages of marine organisms are able to distinguish. Previous experiments showed that Ulva zoospores settle (attach) in high numbers onto fluorinated monolayers compared to PEGylated monolayers. The main aim of the present study was to determine, when zoospores of the green alga Ulva are presented with a choice of fluorinated or PEGylated surfaces, what the minimum dimensions of the two types of surface are that zoospores can detect and consequently settle on. Silicon wafers were chemically modified to produce a pattern of squares containing alternating fluorinated and PEGylated stripes of different widths on either a uniform fluorinated or PEGylated background. Each 1 cm x 1 cm square contained stripes with widths of 500, 200, 100, 50, 20, 5, or 2 microm as well as an unpatterned square with a chemistry opposite that of the background. Spores were selective in choosing where to settle, settling at higher densities on fluorinated stripes compared to PEGylated stripes. However, the magnitude of response, and the consequences for settlement on patterned areas overall, was dependent on both the width of the stripes and the chemistry of the background. The data are discussed in relation to the ability of spores to "choose" favorable sites for settlement and the implications for the development of novel antifouling coatings